(untitled) (Advancements in Homeopathic Research, 2022)
Psoriasis is a common chronic, recurrent, immune mediated disease of the skin and joints. It can have a significant negative impact on the physical, emotional, and, psychosocial wellbeing of affected patients. Psoriasis is found worldwide but the prevalence varies among different ethnic groups. As human being is composed of Mind, Body and Soul and he is free spirited, the organization of it does depend upon the susceptibility. Skin disorders are a very common condition which has affected the lifestyle in many ways. Homeopathy treats person as a whole. So Homoeopathy is effective in skin diseases.